THE TWO PARAMETER SENSORS OF THE LIQUID LEVEL - A. A. Jezhora; V. V. Rubanik (Приборы и методы измерений)
It is considered two parameter the sensors of level of a liquid. The sensors contains three cylindrical electrodes of unequal length. The potential of an average electrode varies. For the control of dielectric properties of a liquid the length of an internal electrode differs from length of two external electrodes. For numerical 3D sensors modelling the method of the integrated equations and mirror displays is used. The program of numerical calculation is realised in MAPLE. Check on adequacy of model to real designs is checked up.